Do Value-Added Estimates Add Value? Accounting for Learning Dynamics - Andrabi, Tahir; Das, Jishnu; Khwaja, Asim Ijaz; Zajonc, Tristan (2012)
Evaluations of educational programs commonly assume that what children learn persists over time. The authors compare learning in Pakistani public and private schools using dynamic panel methods that account for three key empirical challenges to widely used value-added models: imperfect persistence, unobserved student heterogeneity, and measurement error. Their estimates suggest that only a fifth to a half of learning persists between grades and that private schools increase average achievement by 0.25 standard deviations each year. In contrast, estimates from commonly used value-added models significantly understate the impact of private schools on student achievement and/or overstate persistence. These results have implications for program evaluation and value-added accountability system design.